Assessing the cost of laparotomy at a rural district hospital in Rwanda using time‐driven activity‐based costing. Issue 1 (7th February 2018) - Ruhumuriza, J.; Odhiambo, J.; Riviello, R.; Lin, Y.; Nkurunziza, T.; Shrime, M.; Maine, R.; Omondi, J. M.; Mpirimbanyi, C.; de la Paix Sebakarane, J.; Hagugimana, P.; Rusangwa, C.; et al.
Abstract : Background: In low‐ and middle‐income countries, the majority of patients lack access to surgical care due to limited personnel and infrastructure. The Lancet Commission on Global Surgery recommended laparotomy for district hospitals. However, little is known about the cost of laparotomy and associated clinical care in these settings. Methods: This costing study included patients with acute abdominal conditions at three rural district hospitals in 2015 in Rwanda, and used a time‐driven activity‐based costing methodology. Capacity cost rates were calculated for personnel, location and hospital indirect costs, and multiplied by time estimates to obtain allocated costs. Costs of medications and supplies were based on purchase prices. Results: Of 51 patients with an acute abdominal condition, 19 (37 per cent) had a laparotomy; full costing data were available for 17 of these patients, who were included in the costing analysis. The total cost of an entire care cycle for laparotomy was US$1023·40, which included intraoperative costs of US$427·15 (41·7 per cent) and preoperative and postoperative costs of US$596·25 (58·3 per cent). The cost of medicines was US$358·78 (35·1 per cent), supplies US$342·15 (33·4 per cent), personnel US$150·39 (14·7 per cent), location US$89·20 (8·7 per cent) and hospital indirect cost US$82·88 (8·1 per cent). Conclusion: The intraoperative cost of laparotomy was similar to previous estimates, but any plan to scale‐up laparotomy capacity at district hospitals should consider the sizeable preoperative and postoperative costs. Although lack of personnel and limited infrastructure are commonly cited surgical barriers at district hospitals, personnel and location costs were among the lowest cost contributors; similar location‐related expenses at tertiary hospitals might be higher than at district hospitals, providing further support for decentralization of these services. Abstract : The Lancet Commission on Global Surgery recommended that all district hospitals should be able to perform laparotomy, but little is known about the cost of performing laparotomy at a district hospital in sub‐Saharan Africa. A time‐driven activity‐based costing method was used to estimate the overall hospital cost of laparotomy in rural Rwanda at US$1023, driven largely by the cost of medicines (US$358·79, 35·1%) and supplies (US$342·15 (33·4%). These findings advocate for decentralization of laparotomy because infrastructure (US$89·20, 8·7%) and personal costs (US$150·39, 14·7%) were not the barriers as previously hypothesized, and similar resources cost more at tertiary hospitals. Further support for decentralization of laparotomy in Rwanda